The Synergistic Impact of Social Media and Traditional Media on Purchase Decisions: The Mediating Role of Brand Loyalty - Tarabieh, Saeed M.Z.A. (International Review of Management and Marketing, 2017)
Brand loyalty and purchase decisions are among the central themes of the research for marketers throughout long time. Researchers and brand managers have utilized various means to affect the brand loyalty and purchase decisions of their customers. One of the recent means is social media. Despite that social media gains more importance in businesses, marketers understanding about effectiveness of social media is limited. In fact, the synergistic impacts between social media and traditional media efforts have rarely been investigated. Therefore, this study examines the impact of social media and traditional media on brand loyalty and purchase decisions in the banking industry in Jordan. Structural equation modeling was used in analyzing data obtained, in order to investigate the relationships between the four latent constructs. The empirical analyses of Jordanian banks revealed that a) The effectiveness of social media and traditional media vary, b) The effectiveness of social media on brand loyalty and purchase decisions are significantly higher than what for traditional media, c) Brand loyalty partially mediates the effect of social media and traditional media on purchase decisions, and d) The synergistic effects of social media and traditional media give a better value for brand loyalty and purchase decisions in comparison to the single model, which merely used social media or traditional media. Keywords: Social Media, Traditional Media, Purchase Decisions, Brand Loyalty JEL Classifications: M30, M31